Near-infrared organic light-dependent resistor based on naphthalocyanine - Zhang, Chen; Syed Mohd Jaafar, Syed Muhammad Hafiz; Abd Aziz, Aiman Sajidah; Rejal, Siti Zuulaika; Alserhan, Mhanna; Roslan, Nur Adilah; Supangat, Azzuliani (American Chemical Society, 2026)
This paper presents a near-infrared (NIR) organic light-dependent resistor (OLDR) utilizing 5,9,14,18,23,27,32,36-octabutoxy-2,3-naphthalocyanine (ONc) as the photoactive material, and investigates the influence of preparation parameters on device performance. A flexible interdigitated electrode configuration is employed to fully leverage the excellent mechanical flexibility of organic semiconductor materials. ONc exhibits strong NIR absorption near 924 nm, enabling effective photoresponse under low-light conditions. The device displays typical LDR characteristics and operates stably at a low bias of 2 V, meeting the requirements of optical sensors for low-power, high-response operation. Fabrication is conducted via solution processing, with performance tuning achieved by varying ONc concentration (1–15 mg/mL) and annealing temperature (room temperature to 100 °C). Optimal performance is obtained at a concentration of 10 mg/mL and an annealing temperature of 50 °C, yielding a photocurrent of 52.084 nA under a light intensity of 40.5 mW/cm2. The response and recovery times are 2.173 and 2.185 s, respectively, accompanied by a significant change in resistance of 68.63%. Furthermore, the study explores carrier transport mechanisms and interfacial behavior through morphological analysis and energy-level simulations, providing both theoretical insights and practical guidelines for the development of high-performance, flexible NIR OLDRs.